‘They’re Going to Smoke Anyway’: A Qualitative Study of Community Mental Health Staff and Consumer Perspectives on the Role of Social and Living Environments in Tobacco Use and Cessation - Twyman, Laura; Cowles, Carla; Walsberger, Scott C.; Baker, Amanda L.; Bonevski, Billie; , the Tackling Tobacco Mental Health Advisory Group; Ko, Karina; Oldmeadow, Christopher; Lawn, Sharon; Weber, Marianne; Bowman, Jennifer; Hefler, Marita; et al. (Frontiers in Psychiatry, 2019)
Background Addressing the high prevalence of tobacco use experienced by people with severe mental illness (SMI) requires consideration of the influence of wider cultural, socioeconomic and environmental factors. This qualitative study aimed to examine the impact of social and living environments on tobacco use and cessation by people with SMI accessing community managed mental health services. The perspectives of both staff and consumers with SMI were explored. Methods Semi-structured focus groups were undertaken with a purposive sample of community mental health staff and consumers from three sites in three major cities in NSW, Australia. Two sites provided outreach support and one site provided residential support. Data were collected (2017-2018) until saturation was reached. Focus groups were audio-recorded, transcribed and thematic analysis was conducted. Results Thirty-one staff and 17 consumers participated separately in six focus groups. Themes identified by staff included a degree of fatalism, conceptualising tobacco use as choice rather than addiction, and tensions between cessation support and broader models of care. Staff viewed smoke-free home and mental health service policies as effective at promoting quitting, but contradictory to recovery-oriented models of care. Consumers identified smoking as an integral part of life and social networks, as a way of maintaining control and lack of social support to quit as key themes. While many consumers reported smoking inside the home, others described enforcing smoke-free rules. Conclusion Social and living environments played an integral role in tobacco use and cessation for both staff and consumers. The role of community mental health organisations in addressing tobacco use within social and living environments was not strongly supported by staff and sometimes seen as antithetical to recovery-oriented models of care. Potential ways to address this include education and training for prospective and current CMO staff highlighting the synergy between the recovery-oriented model and provision of preventive health support.